Smart Internet of Things System for Hydroponic - Mazlan, Muhammed Yusuf; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2023)
A hydroponic system is a kind of plantation that uses water as the medium rather than soil. To assist in the development of urban agriculture, a large variety of smart automatic watering solutions have been introduced. These systems, however, are still not included in the action to apply controller water nutrient level, which is essential for boosting overall plant growth. In this paper, the technology is built by combining a typical farming system with a web interface for monitoring the status of the hydroponic system. First, the prototype was built, developed, and tested, and the sensor collected the data and analyze the results on a cloud-based web page through a mobile application. Next, the system is provided with LED indicators to show the current status of water nutrient level solutions to regulate supply chains. By producing the product from an outdoor plant, the user will be able to develop hydroponic plants in their home, requiring just a little amount of space. Lastly, the data collected consists of water level has been analyzed. According to the results, when the value of water is empty, LED blue and LED yellow will turn off, and LED red will turn on, with the LCD displaying "Water level: Low". When the water level is full, LED blue turns on while LED red and LED yellow turn off including the LCD indicator "Water level: High". The system is operational 24 hours a day and power consumption is 22.86 watts. These results showed that the product worked as expected and the overall cost of this project is RM1111.40.